EFEITO ADJUVANTE DOS TOCOFERÓIS NA QUIMIOTERAPIA COM CICLOFOSFAMIDA INDUZ À IMUNOMODULAÇÃO PRÓ Th1. - VALE, André Alvares Marques (2022)
The use of vitamins in the prevention and treatment of cancer has always raised doubts about their effectiveness and, in this controversial context, tocopherols or vitamin E vitamers are also included. The main objective of this work was to evaluate the effects of a mix of tocopherols on tumor development in in vitro and in vivo models, focusing on the processes of immunomodulation and cellular activation, resulting in two articles. In the first article, the ability of tocopherol supplementation to promote a positive outcome in the oncological context was evaluated. For this, the Ehrlich solid tumor model (ET) was applied to Swiss mice and separated into experimental groups (n=7): Control group (NC), Cyclophosphamide group (PC), treated with 25 mg/kg intraperitoneally; Pre- and post-tumor supplementation group (CS), treated with 100mg/kg/day tocopherols orally (v.o.) for 14 days before and 16 days after tumor inoculum; Post-tumor supplementation group (TS), treated with 100mg/kg/day, v.o. of tocopherols after 2 days of tumor inoculum, for 15 days. Throughout the experiment, nutritional data and the volume of the paw with the tumor were collected. After euthanasia, samples were collected for analysis of hematological parameters, production of nitric oxide (NO) and splenocyte phenotyping, in addition to the production of cytokines by the tumor microenvironment in ex vivo culture. The data showed that, regardless of the time of supplementation, tocopherols were able to increase the number of leukocytes and erythrocytes in the blood, however without changing the leukocyte activation phenotype. The animals supplemented before and after the ET inoculum showed an increase in the tumor with production of inflammatory cytokines (IL-12, IFN- and MCP-1) and lower concentration of IL-10, which seems to justify the higher production of NO. Thus, this study confirms the inertia of tocopherol supplementation in the prevention and/or treatment of cancer, however its immunomodulatory action opens an interesting perspective not only in the context of cancer, as well as with other inflammatory diseases. The second article studies the action of tocopherol supplementation as an adjuvant in neoplastic chemotherapy. For this, in vitro analyzes were carried out evaluating possible direct effects of tocopherols on tumor cells and the in vivo assay with Ehrlich'ssolid tumor model under treatment with cyclophosphamide. The results obtained with the tumor lineage ruled out a direct cytotoxic effect of tocopherols, excluding a chemotherapeutic action. In the in vivo assay, it was possible to observe that supplementation reduces cachexia, leukopenia and anemia in animals with ET undergoing cyclophosphamide treatment, without modifying its antineoplastic action. Furthermore, supplementation showed greater activation of cytotoxic lymphocytes (CD3; CD8; CD69), macrophages (CD14; CD69) and natural killer cells (NK 1.1; CD86) in the spleen. This cellular pattern corroborates the Th1 pattern of cytokines (IL-12 and IFN- ) regulated by IL-10. In plasma, lower IL-6 production may reinforce the Th1 pattern and mitigate cancer/chemotherapy-associated cachexia. The data suggest that tocopherol-mediated immunomodulation promotes a Th1 pattern associated with the action of resetting the immune response caused by cyclophosphamide. Considering that the Th1 response is favorable to the elimination of tumor cells, it is speculated that supplementation with tocopherols induces an antitumor immunocompetence and minimizes the harmful effects of chemotherapy.